Calibration and operation of a fibre Bragg grating temperature sensing system in a grid‐connected hydrogenerator. Issue 1 (1st January 2013) - Werneck, Marcelo Martins; Allil, Regina Célia da Silva Barros; Ribeiro, Bessie A.
Abstract : There have been many applications of fibre Bragg grating (FBG) in temperature measurements; however, there are no studies concerned with their application, uncertainty and repeatability as temperature sensor in the electric power industry. This study describes the research, construction, calibration and operation of an FBG‐based temperature system performing a continuous monitoring of temperature inside a fully operational and connected‐to‐the‐grid hydroelectric generator. The FBGs were calibrated for quantification of parameters such as uncertainty, sensitivity, linearity and error. The plot of calibrating temperature against measured temperature presented a one‐to‐one fitting accuracy to the third decimal place, uncertainty errors smaller than 1°C and a correlation coefficient R 2 = 0.99996, demonstrating good linearity and accuracy of FBG sensors for temperature measurements. After being deployed for 2.5 years, the system has proved itself to be capable of reliably and accurately measuring and monitoring temperatures inside the generator, even taking into consideration the harsh environment. Results showed that the optical system provides a better electromagnetic interference immunity when compared with conventional temperature sensors. With this system in operation, a huge amount of installation and maintenance costs could be avoided with the replacement of many kilometres of electric wires by a few optical cables.